STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI TOLERANSI ANTAR UMAT BERAGAMA - Zainur Rohman; Ahmad Izza Muttaqin; Nasrodin Nasrodin (Tarbiyatuna Kajian Pendidikan Islam, 2023)
This research focuses on describing how the strategies used by education teachers in instilling the values of inter-religious tolerance and how the condition of students' inter-religious tolerance. The approach used in this research is descriptive qualitative. The subjects in this study were Islamic religious education teachers and grade vii students and documents as supporting data. The data in this study were obtained through interviews, observations and documentation then the data were analyzed through data reduction, data presentation, and verification and checked the validity of the data using the source triangulation method. The results in this study show that Islamic religious education teachers use several strategies in instilling inter-religious tolerance values, namely: 1. Learning through textbooks. 2. habituation. 3. Exemplary 4. Guidance. In addition to the strategies carried out by Islamic religious education teachers, schools also implement habituation in instilling the values of inter-religious tolerance of students, namely with SAS (Peer Fostered Students) and Friday Taqwa.